MILITARYPOLITICAL RELATIONS IN THE TRIANGLE US — TURKEY — FRANCE: 2009–2012 - V. A. Avatkov; A. O. Domanov (Сравнительная политика)
The article explores interaction in the U.S.-Turkey-France triangle on military and political issues related to the rejoining of NATO military organization by France in 2009. This analysis is important to clarify the level of NATO coherence, speed of the emergence of polycentric world and to forecast behavior of these three partners. The article studies differences in doctrines and approaches of the three countries to the Iranian, Syrian, Libyan and Afghan crises. In regards to each of the crises interests of three countries are identified, which define their poitions. The authors come to the conclusion that existing differences are not deep and reflect divergent rather than antagonistic interests.